Resilience, Hope, and Subjective Happiness Among the Turkish Population: Fear of COVID-19 as a Mediator - Satici, Seydi Ahmet; Kayış, Ahmet Rıfat; Sat?c?, Beg?m; Griffiths, Mark D.; Can, Gurhan (Springer, 2020)
Psychology deals with not only mental disorders but also psychological strengths within individuals. Psychological strengths will play an important role in struggling with the global novel coronavirus 2019 (COVID-19) pandemic. The present study tested a model concerning the relationship between resilience, hope, and subjective happiness using structural equation modeling to identify the mediating role of fear of COVID-19. A cross-sectional survey was conducted among a convenience sample of 971 Turkish individuals (aged 18 to 74 years) from 75 of 81 cities in Turkey. The survey included the Subjective Happiness Scale, Fear of COVID-19 Scale, Brief Resilience Scale, and the Dispositional Hope Scale, and data were analyzed using structural equation modeling (SEM). The SEM demonstrated an association between resilience–hope and subjective happiness was mediated by fear of COVID-19 (CMIN/df = 2.664, CFI = 0.994, NFI = 0.984, TLI = 0.984, GFI = 0.994, RMSEA = 0.044, SRMR = 0.024, AIC = 81.334, ECVI = 0.084). Resilience had a direct effect and an indirect effect on subjective happiness via fear of COVID-19. Hope also had a direct effect and an indirect effect on subjective happiness via fear of COVID-19. Consequently, in the fight against COVID-19, individuals who are resistant to stress and have a belief that they can find a way to cope can help prevent the fear of COVID-19 and so enhance good mental health. © 2020, The Author(s).
Keywords: COVID-19; Fear of COVID-19; Hope; Resilience; Subjective happiness